Establishing an ant-plant mutualism: foundress queen mortality and acquiring the third partner (2016)
In the Neotropics, colonies of the ant Pseudomyrmex dendroicus are found in the hollow stems of Triplaris americana. The ants are obligate inhabitants of the ant-plant and they nest and reproduce exclusively in this myrmecophyte. However, this mutualistic association often involves a third partner, scale insects (Coccoidea, Hemiptera). Established colonies of this ant are always associated with scale insects and ants appear to be dependent on the honeydew excretions of their trophobionts. Acquisition of scale insects is therefore an important step in the successful establishment of a new colony. Domatia of juvenile host-plants were dissected to determine (1) how colonies are founded, (2) if there was evidence of co-dispersal between trophobionts and foundress queens. Colony foundation is claustral. Founding queens of Pseudomyrmex chew their entrance holes at the prostoma and then close the hole with debris. 104 queens were located with few or no workers. Of the 104 foundresses, 69 were found dead and only 32 had at least a single trophobiont. Although the association with trophobionts may prove vital to the establishment of the colony, these results indicate that scale insects do not seem to co-disperse with the foundress queens. © 2015, International Union for the Study of Social Insects (IUSSI).